Ion channels in lung cancer: biological and clinical relevance - Capitani, Chiara; Chioccioli Altadonna, Ginevra; Santillo, Michele; Lastraioli, Elena (Frontiers in Pharmacology, 2023)
Despite improvements in treatment, lung cancer is still a major health problem worldwide. Among lung cancer subtypes, the most frequent is represented by adenocarcinoma (belonging to the Non-Small Cell Lung Cancer class) although the most challenging and harder to treat is represented by Small Cell Lung Cancer, that occurs at lower frequency but has the worst prognosis. For these reasons, the standard of care for these patients is represented by a combination of surgery, radiation therapy and chemotherapy.In this view, searching for novel biomarkers that might help both in diagnosis and therapy is mandatory.In the last thirty years it was demonstrated that different families of ion channels are overexpressed in both lung cancer cell lines and primary tumours. The altered ion channel profile may be advantageous for diagnostic and therapeutic purposes since, most of them being are localised on the plasma membrane, thus their detection is quite easy, as well as their block with specific drugs and antibodies. This review focuses on ion channels (Potassium, Sodium, Calcium, Chloride, and Anion and Nicotinic Acetylcholine receptors) in lung cancer (both Non-Small Cell Lung Cancer and Small Cell Lung Cancer) and recapitulate the up-to-date knowledge about their role and clinical relevance for a potential use in the clinical setting, for lung cancer diagnosis and therapy. This is a provisional file, not the final typeset article scarce cytoplasm, little or no nucleoli and "salt and pepper" chromatin pattern (Nicholson et al., 2002). 60Mitotic figures are a frequent finding and necrotic areas are also quite common and extensive. For 61 SCLC, the diagnosis is determined by both light and electron microscopy (to detect neuroendocrine 62 granules) complemented by immunohistochemistry for neuroendocrine markers (chromogranin and 63 synaptophysin) (Righi et al., 2022). The presence of neuroendocrine markers highlights the 64 neuroendocrine origin of SCLC. The main clinical and molecular features of NSCLC are reported in 65 Table 1. 66 SCLC are the most aggressive LC, extensively metastasize, are virtually incurable by surgery and show 67 a close relationship to smoking.